2015
DOI: 10.1039/c5ra19421k
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent biosensor of lysozyme-stabilized copper nanoclusters for the selective detection of glucose

Abstract: Fluorescent copper nanoclusters (Lys-CuNCs) were synthesized using lysozyme as a template, displaying smart response to glucose concentration with high sensitivity. The visualization variation of Lys-CuNCs may further enable the rapid and simple detection of blood glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…Thus the lyz-CuNCs reported in this paper exhibited a shift of 60 nm in their fluorescence emission when compared to the blue lyz-CuNCs reported in the literature. 13 Thus, our green fluorescent lyz-CuNCs complement the blue 13 and red 14 nanoclusters reported in the literature by completing the range of emission of 450 to 600 nm via bridging the gap with its emission centered at 510 nm. As compared to other pH conditions studied, at pH = 7, the agglomeration is prevented due to the capping of lyz that results in exhibiting significant fluorescence emission intensity at 510 nm ( Fig.…”
Section: View Article Onlinesupporting
confidence: 69%
See 2 more Smart Citations
“…Thus the lyz-CuNCs reported in this paper exhibited a shift of 60 nm in their fluorescence emission when compared to the blue lyz-CuNCs reported in the literature. 13 Thus, our green fluorescent lyz-CuNCs complement the blue 13 and red 14 nanoclusters reported in the literature by completing the range of emission of 450 to 600 nm via bridging the gap with its emission centered at 510 nm. As compared to other pH conditions studied, at pH = 7, the agglomeration is prevented due to the capping of lyz that results in exhibiting significant fluorescence emission intensity at 510 nm ( Fig.…”
Section: View Article Onlinesupporting
confidence: 69%
“…In the case of blue fluorescent lyz-CuNCs, 2 to 9 copper bound nanoclusters (Cu 2 , Cu 4 and Cu 9 ) were reported, 13 while no MALDI studies were reported in the case of red lyz-CuNCs. 14 An FTIR spectrum of simple protein shows an amide peak at B1600 cm À1 along with a shoulder at B1700 cm À1 . In the case of lyz-CuNCs, only the shoulder disappears and the amide band is retained, suggesting the capping of CuNCs by the protein, lysozyme.…”
Section: Characterization By Maldi and Ftir Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many efforts have led to some approaches for Cu NCs syntheses such as polymer and biomolecule templated methods [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], electrochemical reduction [ 32 ], sonochemical synthesis [ 33 ], microwave-assisted [ 34 , 35 , 36 ] and microemulsion technology [ 37 , 38 ]. However, those as-prepared Cu NCs are mostly dispersed in homogeneous solution.…”
Section: Introductionmentioning
confidence: 99%
“…In biomolecule detection, the lysozyme functionalized fluorescent copper nanoclusters (Lys-Cu NCs; Φ = 5.6%)-based glucose sensor viaa fluorescence quenching effect was reported by Wang et al [147]. Lys-Cu NCs displayed the two linear response ranges with glucose between 0.03-10 μM and 0.5-10 mM with an LOD of 1.9 nM.…”
Section: Sensor Applications Of Cu Ncsmentioning
confidence: 99%